Information Avoidance - Golman, Russell; Hagmann, David; Loewenstein, George (Journal of Economic Literature, 2017)
We commonly think of information as a means to an end. However, a growing theoretical and experimental literature suggests that information may directly enter the agent's utility function. This can create an incentive to avoid information, even when it is useful, free, and independent of strategic considerations. We review research documenting the occurrence of information avoidance, as well as theoretical and empirical research on reasons why people avoid information, drawing from economics, psychology, and other disciplines. The review concludes with a discussion of some of the diverse (and often costly) individual and societal consequences of information avoidance. (JEL D82, D83)